Urethral realignment with maximal urethral length and bladder neck preservation in robot-assisted radical prostatectomy: Urinary continence recovery - Heo, Ji Eun (PLoS One, 2020)
PURPOSE: To evaluate early recovery of urinary continence after robot-assisted radical prostatectomy (RARP) with urethral realignment using bladder neck preservation (BNP) and maximal urethral length preservation (MULP). METHODS: Patients who underwent RARP between 2014 and 2017 owing to prostate cancer with a Gleason score ≤ 7 (3+4), ≤ cT2c stage, and prostate-specific antigen level < 20 ng/ml were investigated. Patients with tumors of the bladder neck or apex on magnetic resonance imaging were excluded. A total of 266 patients underwent the operation using the standard method between 2014 and 2015 (group 1), while 305 patients underwent urethral realignment between 2016 and 2017 (group 2). Continence was defined as wearing no pad or one security pad. RESULTS: The continence rates immediately after Foley catheter removal, at 2 weeks, and at 1, 3, 6, and 12 months after operation in group 2 were 46.9%, 63.0%, 73.4%, 90.1%, 94.8%, and 98.7%, respectively. The continence rate at 1 month in group 2 was significantly higher than that in group 1 (65.4% versus 73.4%, p = 0.037). The multivariate regression analysis showed that age and surgical method were factors affecting early continence recovery. The positive surgical margin rates were 18.0% and 14.8% in groups 1 and 2, respectively (p = 0.288). Biochemical recurrence occurred in 14.7% and 8.2% in groups 1 and 2, respectively (p = 0.015). CONCLUSION: Urethral realignment using BNP and MULP resulted in rapid continence recovery and good oncological results after RARP in young patients with a Gleason score ≤ 7 and organ-confined disease.